Neue regulatorische Konzepte der Bankenaufsicht und ihre Auswirkungen auf die Gesamtbanksteuerung - Tim Noack; Heinz Cremers; Julia Mala (Frankfurt School of Finance & Management, 2014)
– The Basel III framework represents the response to the regulation deficits of the financial cri-sis and the immense losses of many banks in years 2007/2008. The aim of the framework is to increase the level of capital in financial institutions and to improve the loss absorption and risk coverage of capital. With its' implementation in the European Union in form of a Regulation, which came into force in January 2014, the framework will cause massive capital short-falls, forcing banks to rethink their capital structure and improve their capital management. Furthermore the Basel III implementation will have noticeable effects on banks' profitability, their costs of capital as well as their business models. This Working Paper presents the measures of the new regulatory framework and discusses potential impacts on the overall bank management.
Keywords: G00; G01; G18; G28; G29; F33; 330; Basel III; CRR; own funds; Leverage Ratio; Liquidity Coverage Ratio; Net Stable Funding Ratio; Monitoring Tools; CVA Charge; Central Counterparty; Counterparty Credit Risk; basel committee on banking supervision; EPE models; capital requirements; capital conservation buffer; additional capital buffers; additional capital buffers for G-SIFIS; transitional arrangement; consequences on solvability; consequences on liquidity; consequences Leverage Ratio